Assistance in the implementation of occupational safety and health towards halal certification for small and medium enterprise - Aisyah, Iis Siti; Ma’arif, Moch. Syamsul; Daryono, D.; Budiono, B. (Journal of Community Service and Empowerment, 2023)
Pawon Ning Nur is one of the UMKM affected by Covid19, because students have returned to their hometowns. So that what was originally a business in the form of a food stall, has turned into a frozen food business, especially Bandeng Otak-otak. Marketing difficulties due to not having a Halal certificate prompted the team to provide assistance. The team consists of lecturers and students of PMM-Mitra Dosen. The objective this activity was to familiarize Occupational Safety and Health when pursuing for halal certification of Small and Medium Enterprise. The methods consist of administrative assistance for registration of halal certificates, assistance when inspections are carried out by BPOM, helping to fulfill requirements and findings, as well as conducting OSH training, and providing assistance with production equipment. The results were obtained which satisfied UMKM partners because the activities fulfilled several aspects, Partners obtain Halal Certificates with the number LPPOM JI-07030005171221. Partners have understood and implemented Occupational Health and Safety (OSH). Partners also received safe production equipment donation.